Financial integration and emerging markets capital structure - LUCEY, BRIAN MICHAEL (My University, 2011)
This paper investigates the impact of country-level financial integration on corporate financing choices in emerging economies. Examining 4477 public firms from 24 countries, we find that corporate leverage is positively related to credit market integration and negatively related to equity market integration. As integration proceeds to higher levels, high-growth firms seem to obtain more debt than low-growth firms; large firms seem to obtain more debt ? especially long-term debt ? and issue more equity than small firms. Also, there is evidence that firms are able to borrow more funds in countries with more efficient legal systems during integration process.
PUBLISHED
Keywords: Economics; emerging markets